Downregulation of ACE2/Ang-(1–7)/Mas axis promotes breast cancer metastasis by enhancing store-operated calcium entry. Issue 2 (1st July 2016) - Yu, Changhui; Tang, Wei; Wang, Yuhao; Shen, Qiang; Wang, Bin; Cai, Chunqing; Meng, Xiaojing; Zou, Fei
Highlights: ACE2 expression is downregulated in breast cancer. ACE2 expression is negatively correlated with metastasis from breast cancer. Inhibition of ACE2/Ang-(1–7)/Mas axis stimulates migration and invasion of breast cancer cells. Activated ACE2/Ang-(1–7)/Mas axis inhibits breast cancer cell migration and invasion. Downregulated ACE2/Ang-(1–7)/Mas axis promotes SOCE and PAK1/NF-κB/Snail1 pathways and inhibits E-cadherin expression. Abstract: The renin–angiotensin system (RAS) is an important component of the tumor microenvironment and plays a key role in promoting cancer cell proliferation, angiogenesis, metabolism, migration and invasion. Meanwhile, the arm of angiotensin-converting enzyme (ACE)2/angiotensin-(1–7) [Ang-(1–7)]/Mas axis in connection with RAS is associated with anti-proliferative, vasodilatory and anti-metastatic properties. Previous studies have shown that Ang-(1–7) reduces the proliferation of orthotopic human breast tumor growth by inhibiting cancer-associated fibroblasts. However, the role of ACE/Ang-(1–7)/Mas axis in the metastasis of breast cancer cells is still unknown. In the present study, we found that ACE2 protein level is negatively correlated with the metastatic ability of breast cancer cells and breast tumor grade. Upregulation of ACE2/Ang-(1–7)/Mas axis inhibits breast cancer cell migration and invasion in vivo and in vitro . Mechanistically, ACE2/Ang-(1–7)/Mas axis activation inhibits store-operated calcium entry (SOCE) and PAK1/NF-κB/Snail1 pathways, and induces E-cadherin expression. In summary, our results demonstrate that downregulation of ACE2/Ang-(1–7)/Mas axis stimulates breast cancer metastasis through the activation of SOCE and PAK1/NF-κB/Snail1 pathways. These results provide new mechanisms by which breast cancer develop metastasis and shed light on developing novel anti-metastasis therapeutics for metastatic breast cancer by modulating ACE2/Ang-(1–7)/Mas axis.